Larvicidal Activity of Chemically Synthesized Silver Nanoparticles Against Anopheles stephensi (Journal of Pharmaceutical Negative Results, 2019)
Background: Silver nanoparticles (AgNPs) have wide applications in different fields such as medicine, food industry, and pest management.Larvicidal activity of many herbally biosynthesized AgNPs have been evaluated against main malaria vector, that is, Anopheles stephensi.However, results of the studies are very different. No report has been found on larvicidal activity of chemically synthesized AgNPs againstA. stephensi. Materials and Methods: AgNPs were synthesized using chemical reduction and characterized by dynamic light scattering andtransmission electron microscopy. Concentration of silver ion in the final solution was determined by ICP‑AES. Turbidity of solutions ofAgNPs at different concentrations(i.e., 0.2–100 ppm) was studied. Subsequently, larvicidal activity of nanoparticles was evaluated, in line withthe WHO guideline for laboratory tests. Results: AgNPs were synthesized successfully and confirmed by ultraviolet analysis. Nanoparticleswere spherical with a diameter of ~30 nm. AgNPs had no larvicidal activity up to 80 ppm and showed a small larvicidal effect (~20%) at100 ppm. Conclusion: Chemically synthesized AgNPs are not proper candidates for control of larvae due to their low efficacy and effects onnontarget specious lived in stagnant water.